A quick, easy, cheap, effective, rugged, and safe method for the simultaneous detection of four triazolone herbicides in cereals combined with ultrahigh performance liquid chromatography with tandem mass spectrometry. Issue 17 (15th July 2014) - Tao, Yan; Xu, Jun; Liu, Xingang; Cheng, Youpu; Liu, Na; Chen, Zenglong; Dong, Fengshou; Zheng, Yonguan
<x xml:space="preserve">Abstract</x> This paper describes a novel, rapid, and sensitive analytical method for monitoring four triazolone herbicides in cereals (wheat, rice, corn, and soybean), using a quick, easy, cheap, effective, rugged, and safe sample extraction procedure followed by ultrahigh performance liquid chromatography coupled with tandem mass spectrometry. The four triazolone herbicides (amicarbazone, carfentrazone‐ethyl, sulfentrazone, and thiencarbazone‐methyl) were extracted using acidified acetonitrile (containing 1% v/v formic acid) and subsequently purified with octadecylsilane (C18) prior to sample analysis. Ultrahigh performance liquid chromatography coupled with tandem mass spectrometry was operated in positive and negative ionization switching mode. Amicarbazone and carfentrazone‐ethyl were detected in the positive mode (ESI+), while sulfentrazone and thiencarbazone‐methyl were detected in the negative mode (ESI−). All compounds were successfully separated in less than 3.0 min. Further optimization achieved desired recoveries ranging from 74.5 to 102.1% for all analytes with relative standard deviation values ≤17.2% in all tested matrices at three levels (10, 100, and 500 μg/kg). The limits of detection for all compounds were ≤2.3 μg/kg, and the limits of quantitation did not exceed 7.1 μg/kg. The developed method showed excellent linearity (R2 ≥ 0.994) and was proven to be highly efficient and reliable for the routine monitoring of triazolone herbicides in cereals.